PENGEMBANGAN E-LKPD BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Gilang Asri Pratiwi; Aryo Andri Nugroho; Ngatmini (STKIP Subang, 2023)
The purpose of this development research was to determine the validity, practicality, and effectiveness of the PBL-based E-LKPD to improve the Mathematical Problem-Solving Ability of Class V Students at SDN Batiombo 01. This research was research and development with a design from Borg and Gall. The instruments used were validity sheets for experts and practitioners, teacher and student response questionnaires, E-LKPD validation sheets, validation sheets for solving mathematical problem solving skills, pretest and posttest questions. The validity test was carried out by experts with a value of 87.5% in the very valid category. The practicality test which was stated as practical by students with a score of 82 in the very good category and the practicality/readability response of the practitioner by the class teacher obtained a score of 83.75 in the very good category, and peer assessment obtained a score of 86.26 in the very good category. The effectiveness test used is the paired sample t test and n-gain. The result of the paired sample t test is 0.000, which means that there is an average difference between the learning outcomes of the pretest and posttest, which means the use of PBL-based E-LKPD to improve the mathematical problem solving ability of fifth grade elementary school students. The N-Gain result is 0.63 in the medium category.